Complications arising from maxillary sinus raising (Research, Society and Development, 2022)
In a rehabilitative and aesthetic way, the science of implantology has improved in order to solve some discomforts reported by patients. Among these complaints, the edentulous areas must be meticulously evaluated for adequate clinical planning. Therefore, when the atrophic maxilla is diagnosed, in most cases the maxillary sinus ends up pneumatizing and operational techniques are analyzed to allow the accommodation of the implants. For this reason, the objective of this study is to report the main complications resulting from the maxillary sinus lift procedure. For the elaboration of the research, a bibliographic survey was carried out, using the Scientific Electronic Library Online (Scielo) and Medical Literature Analysis and Retrieval System Online (Medline) databases. Specific descriptors such as maxillary sinus floor elevation, intraoperative complications and maxilla were used as the search method. In this research, the articles were selected by appropriate criteria relevant to the theme, all published between 2016 and 2022, in English and Portuguese. In the current literature, there are many studies in this area that prove a high success rate in maxillary sinus lift surgeries, however, as with any surgical intervention, operational risks may be present. In this aspect, when some questions are added, such as good scientific knowledge on the subject, manual dexterity of the operator and respect for each individual's compliance, the probability of complications from the surgery decreases.